(untitled) - Silberberg, Martin S. (Boston, 2010)
Silberberg’s Principles of General Chemistry offers students the same authoritative topic coverage as his 4th edition textbook while appealing to today’s efficiency-minded and value-conscious instructors and students. Principles allows for succinct coverage of content with minimal emphasis on pedagogic learning aids. This new approach offers a more straightforward approach to learning the core principles without sacrificing depth, clarity, or rigor
Anh Văn chuyên ngành Sư phạm Hóa,Hóa học đại cương 2
Keywords: Chemistry; Hóa học